Crowdfunding Data as a Source of Innovation - Volker Bilgram; Oliver Gluth; Frank T. Piller (Marketing Review St.Gallen, 2017)
In the digital era, crowdfunding platforms serve as a litmus test for the desirability and viability of thousands of innovative ideas. Based on consumers' actual purchasing behavior, crowdfunding data promises to reveal future hot topics and technologies. This study shows how companies can identify innovation opportunities from crowdfunding data by applying machine learning techniques.
Keywords: 650